Mobile Learning: Innovation in Teaching and Learning Using Telegram - Zanaton H. Iksan; Sumaiyah Mohd Saufian (International Journal of Pedagogy and Teacher Education, 2017)
Innovation in teaching and learning is always done by the teachers to solve the problems. Teachers could use the latest education tools as their innovation. Attendance and students’ engagement are the problems in a class and it could be overcome by using mobile learning as a teaching approach. In this case, Telegram is a tool for mobile learning. The aim of this study was to explore how Telegrams could be used in teaching and learning process. This study involved a case study approach where 31 students were the participants in the post graduate courses "Science Education and Human Development". Data were collected by Telegram discussion. This study found that several techniques can be carried out using Telegram: attendance, one way discussions, technique 1-2-3 discussion, pictures, drawing, and audio. Students responded that the teaching and learning using Telegram allow them to gain new experience, be more creative, generate spontaneous ideas, provide authentic ideas without the risk of being humiliated and encourage them to be excited as well as passionate with their learning. Compared with normal classes, all students can give ideas and the ideas were honest by themselves. This study implies that the latest innovation could solve the teaching according to the problems faced by teachers. Except where otherwise noted, content on this site is licensed under a Creative Commons Attribution 4.0 International License